2002
DOI: 10.1590/s1519-69842002000200019
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal processes in Salto Grande reservoir (Americana, SP, Brazil) and its influence in the formation of compartment system

Abstract: Studies on the longitudinal processes in reservoirs, involving physical, chemical and biological processes have been thoroughly appraised, suggesting the existence of a longitudinal organization controlled by the entrance and circulation of water which inserts modifications in the structuring of the system. To evaluate this effect, the Salto Grande reservoir (Americana, SP) was analyzed in 11 sampling stations in its longitudinal axis, in the rainy and dry seasons of 1997 considering the physical chemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 3 publications
5
8
0
6
Order By: Relevance
“…Variation in the nutrient contents along the longitudinal gradient was already observed in several reservoirs, as in Segredo (Thomaz et al, 1997) and Salto Grande (Zanata and Espíndola, 2002). In the present study, similarity among the sampling sites of each reservoir was observed.…”
Section: Discussionsupporting
confidence: 85%
“…Variation in the nutrient contents along the longitudinal gradient was already observed in several reservoirs, as in Segredo (Thomaz et al, 1997) and Salto Grande (Zanata and Espíndola, 2002). In the present study, similarity among the sampling sites of each reservoir was observed.…”
Section: Discussionsupporting
confidence: 85%
“…followed a similar longitudinal gradient reaching highest www.revhydro.com densities in the transition zone and lower in the lacustrine zone (URABE and MURANO, 1986;URABE, 1989). Copepods, on the other hand, were more abundant in the lacustrine zone (ZANATA and ESPÍNDOLA, 2002). The longitudinal distribution of rotifers in Xiangxi Bay was similar with the research of ZANATA and ESPÍNDOLA (2002) and densities were the highest in the transition zone, followed by the lacustrine and then in the riverine zone.…”
Section: Spatial Heterogeneitysupporting
confidence: 76%
“…The longitudinal distribution of rotifers in Xiangxi Bay was similar with the research of ZANATA and ESPÍNDOLA (2002) and densities were the highest in the transition zone, followed by the lacustrine and then in the riverine zone. Rotifer density was greater in the transition zone, which was often observed by other authors (SEDA and DEVETTER, 2000;ZANATA and ESPÍNDOLA, 2002). This may be due to the transition zone having a lower current velocity than the riverine zone and supporting autochthonous organisms instead of allochthonous ones.…”
Section: Spatial Heterogeneitysupporting
confidence: 70%
“…Os reservatórios são ambientes artificias distintos dos ecossistemas aquáticos naturais, pois são diretamente dependentes de mecanismos operacionais implicando em alterações nas características físicas, químicas e biológicas desses ambientes. O fator operacional juntamente com o efeito de forças naturais e do ciclo hidrológico causam uma distribuicão heterogênea das características desse ambiente, sendo possível observar três zonas que se diferenciam enquanto as suas características (Zanata & Espíndola, 2002). Como mencionado, essas zonas são denominadas de fluvial, transição e lacustre.…”
Section: Resultados E Discussão Da Identificação De Motifsunclassified